Ethics in school administration - Kocabas, Ibrahim; Karakose, Turgut (Academic Journals, 2009)
Ethics is a concept about moral values and rules. The principals' ethical leadership is of great importance regarding the educational organizations. The most important responsibility of school principals is to have an ethical perception of school administration. This paper presents a conceptual framework about ethics in school administration. School principals have certain responsibilities and they have to behave ethically while making decisions. The paper emphasizes the necessity of establishing codes of ethics and behaving according to these codes for school leaders. This study gives a brief summary about some ethical dilemmas that school principals faced. Related literature in the study indicates that most principals need professional development in ethical decision-making.
Keywords: Ethics; ethics in education; school principals; school administration